Comparison of different heating materials for the development of an artificial feeding method for aedes albopictus / Mario Joseph - Joseph, Mario (2017)
The rationale of using an artificial membrane feeder is to minimize the use of animals such as rats in direct host feeding method for mosquito blood feeding. This study focuses on testing vegetable oil, water, and glycerol to determine the best heating material to be used in the artificial membrane feeder. This study also compares the feeding and oviposition rates of mosquitoes based on two different feeding method,s namely direct host feeding (DHF) and artificial feeding (AF). The heating materials were tested by pre-heating to ~80°C and ~50°C for heating the blood to 37±1°C and to maintain the temperature at 37±1°C, respectively. The mosquitoes were fed for 15 minutes for both methods and the eggs produced were calculated up to seven days after each feeding session. The feeding and oviposition rates were analyzed by using independent t test. The best heating material was glycerol and there is significant difference for both feeding rate (76.67±6.67% for DHF(r) and 26.67±6.67% for AF) and oviposition rate (43.13±1.59 eggs for DHF and 29.38±2.9 eggs for AF) for both methods where P<0.05, respectively. However, the eggs produced from AF method (235 eggs per 8 mosquitoes) were still sufficient for mosquito colony maintenance, and with increased sample size both parameters are expected to increase. In conclusion, the artificial membrane feeder proposed is sufficient to be used as alternative method in feeding mosquitoes for research purposes.